2013
DOI: 10.1111/jonm.12079
|View full text |Cite
|
Sign up to set email alerts
|

Work climate, work values and professional commitment as predictors of job satisfaction in nurses

Abstract: Nursing management must be careful to keep the context of work tuned to individuals' attitude and vice versa. Improving the work climate can have a positive effect on job satisfaction, but its effect may be enhanced by favouring strong professional commitment and by promoting intrinsic more than extrinsic work values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 79 publications
4
72
0
7
Order By: Relevance
“…The institution or department itself can also affect stress levels. Staff employed at university hospitals evaluated the presence of stress as statistically significant compared to staff employed at general hospitals or specialized hospitals in view of “Organizational Stress Factors” (29). Staff working at a hospital department rated the presence of stress as statistically significant in view of “Management Requirements”, whereby previous studies highlighting Intensive Care Units (ICUs) and Emergency Departments (30, 31, 32, 33, 34, 35, 36) could not have been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The institution or department itself can also affect stress levels. Staff employed at university hospitals evaluated the presence of stress as statistically significant compared to staff employed at general hospitals or specialized hospitals in view of “Organizational Stress Factors” (29). Staff working at a hospital department rated the presence of stress as statistically significant in view of “Management Requirements”, whereby previous studies highlighting Intensive Care Units (ICUs) and Emergency Departments (30, 31, 32, 33, 34, 35, 36) could not have been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, very few studies have accounted for the correlation between work-value orientation and professional identity statuses. Using a sample of nurses, Caricati et al (2014) showed that holding intrinsic more than extrinsic work values drove participants to be more committed to their profession, which in turn enhanced their job satisfaction. Similarly, Marletta et al (2014) found that nurses in the achievement and searching moratorium statuses showed higher intrinsic but also extrinsic motivations than did individuals in moratorium and foreclosure statuses.…”
Section: Work Valuesmentioning
confidence: 98%
“…In addition, job satisfaction can be accounted for a central determinant of turnover, work performance, and outcome and general well-being of workers; therefore, both organizational psychology and nursing management, work climate, professional commitment and work value orientation are considered as important factors. [27] In future, further research is required for experimental investigations to clearly identify the benefits of a transition program compared to the traditional program.…”
Section: Limitationmentioning
confidence: 99%